Auf dem Weg zum ,Einen in uns' bei Proklos und Ioane Petrizi - Khubulava, Tamar (Academia Philosophical Studies, 2022)
The subject of this monograph lies at the intersection of metaphysics, epistemology and the philosophy of action of the late Platonist Proclus and his Georgian commentator from the 11th/12th century, Ioane Petrizi. With Proclus, the theme of the 'One in us' is closely connected both with his metaphysics of the One as the transcendent principle of everything and with his epistemology, which underlines different modes of cognition and their limits parallel to different types of cognitive objects. Finally, it is also connected with his theory of action, which deals with the practical implementation of the gradual ascent of the soul to the transcendent One, or the unification of the soul with the One operating within itself.